Rancang Bangun Sistem Informasi Portal Berita Pada Kementerian Hukum Jambi Berbasis Web - Munir, Alya Khairina; Firmansyah, Kms. Zaldi; Muna, Naylul; Kurniawan, Iwan; Anwari, Muhammad Fazly; Ramadhan, Rizki; Karim, Wajid Nur (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
The problem faced by the Jambi Regional Office of the Ministry of Law related to news portals is that the existing systemis ineffective in presenting the latest and relevant legal information to the public. The old system has disadvantages suchas a less intuitive interface, many features that confuse users, and the absence of interactive features that can involve thepublic in discussions of evolving legal issues. In addition, this portal lacks the legal information needed by the public. Thepurpose of this research is to design and develop a web-based news portal system that can provide up-to-date and relevantlegal information for the people in Jambi Province, with a focus on presenting legal news that is easily accessible andunderstandable. This system aims to replace the old system that has limitations. The methods used in this study includeanalysis of existing systems, data collection through observation, interviews, and documentation, and system design usingUML (Unified Modeling Language). The system is tested using the black-box method to ensure that all features runaccording to the set objectives. The results show that the new news portal system can present legal information moreeffectively with features such as news searches, news categories, and interaction between admins and users. This system isexpected to increase transparency, legal literacy, and provide better access for the public to accurate and up-to-date legalinformation.